Infrapatellar fat pad adipose tissue-derived macrophages display a predominant CD11c+CD206+ phenotype and express genotypes attributable to key features of OA pathogenesis - Hengtrakool, Patchanika; Leearamwat, Nitigorn; Sengprasert, Panjana; Wongphoom, Jutamas; Chaichana, Thiamjit; Taweevisit, Mana; Ngarmukos, Srihatach; Tanavalee, Aree; Palaga, Tanapat; Reantragoon, Rangsima (Frontiers in Immunology, 2024)
Objectives: In knee osteoarthritis (OA), macrophages are the most predominant immune cells that infiltrate synovial tissues and IPFPs. Both M1 and M2 macrophages have been described, but their role in OA have not been fully investigated. Therefore, we investigated macrophage subpopulations in IPFPs and synovial tissues of knee OA patients and their correlation with disease severity, examined their transcriptomics and tested for factors that influenced their polarization.Methods: Synovial tissues and IPFPs were obtained from knee OA patients undergoing total knee arthroplasty. Macrophages isolated from these joint tissues were characterized via flow cytometry. Transcriptomic profiling of each macrophage subpopulations was performed using the Nanostring technology. Peripheral blood monocyte-derived macrophages (MDMs) were treated with synovial fluid and synovial tissue-and IPFP-conditioned media. Synovial fluid-treated MDMs were treated with platelet-rich plasma (PRP) and its effects on macrophage polarization observed.Results: Our findings show that CD11c+CD206+ macrophages were predominant in IPFPs and synovial tissues compared to other macrophage subpopulation (CD11c+CD206-, CD11c-CD206+ and CD11c-CD206-macrophages) of knee OA patients. The abundance of macrophages in IPFPs reflected those in synovial tissues, but did not correlate with disease severity as determined from Mankin scoring of cartilage destruction. Our transcriptomics data demonstrated highly expressed genes that were related to OA pathogenesis in CD11c+CD206+ macrophages than CD11c+CD206-, CD11c-CD206+ and CD11c-CD206-macrophages. In addition, MDMs treated with synovial fluid, synovial tissue-conditioned media or IPFP-conditioned media resulted in different polarization profiles of MDMs. IPFP-conditioned media induced increases in CD86+CD206+ MDMs, whereas synovial tissue-conditioned media induced increases in CD86+CD206-MDMs. Synovial fluid treatment (at 1:8 dilution) induced very subtle polarization in each macrophage subpopulations. PRP was able to shift macrophage subpopulations and partially reverse the profiles of synovial fluid-treated MDMs.Our study provides an insight on the phenotypes and genotypes of macrophages found in IPFPs and synovial tissues of knee OA patients. We also show that the microenvironment plays a role in driving macrophages to polarize differently and shifting macrophage profiles can be reversed by PRP.